PRMT1-dependent regulation of RNA metabolism and DNA damage response sustains pancreatic ductal adenocarcinoma - Virginia Giuliani (Nature Portfolio, 2021)
Arginine methylation by PRMTs is dysregulated in cancer. Here, the authors use functional genomics screens and identify PRMT1 as a vulnerability in pancreatic ductal adenocarcinoma, and further show that PRMT1 regulates RNA metabolism and coordinates expression of genes in cell cycle progression, maintaining genomic stability and tumour growth.